Synthesis of Novel C-Pivot Lariat 18-Crown-6 Ethers and Their Efficient Purification - Jana, Susovan; Suresh, Vallabh; Lepore, Salvatore D. (Synlett, 2015)
The syntheses of various lariat ethers including several not previously reported and their efficient purification are presented. The synthesis route brings together reactions from a variety of previous works leading to a robust and generalized approach to these C-pivot lariats. The main steps are condensation of functionalized diols with pentaethylene glycol ditosylate in the presence of potassium as a templating cation. Purification of the final products was achieved without chromatography by extracting from an aqueous potassium hydroxide solution.
Keywords: 18-crown-6; C-pivot lariat ethers; crown compounds; potassium hydroxide purification; macrocyles